The role of the Internal audit’s role in the Armed Forces and its influence on organisational sustainability: a case study - Ferreira, Pedro; Samagaio, Antonio; Rodrigo Diogo, Tiago (Review of Business Management, 2024)
Purpose – This paper develops a case study focused on the Portuguese Air Force, aiming first to identify the Internal Audit (IA) roles and then analyse its influence on organisation sustainability while exploring the moderating effect of human resources management practices (HRMP). Theoretical framework – This research draws on the empirical work regarding the roles and activities performed by IA in the private sector and human capital theory to assess the effect of HRMP on performance. Design/methodology/approach – The study uses the survey method and data were collected through a questionnaire made available on an electronic platform. This study applies ordinary least squares regression model. Findings – This study shows that IA provides assurance and consulting services and IA is positively related to sustainability orientation, particularly in the governance and social dimensions. The moderating effect of HRMP is only felt in the environmental dimension. Research Practical & Social implications – This study reinforces the literature regarding the relationship between IA effectiveness and sustainability, provides insight into the IA effectiveness reported by the auditors themselves, identifies the portfolio of functions performed by IA and points to improvements to be made in IA management. Originality/value – The topics studied are for the first time explored in the context of the armed forces and is pioneering in analysing the moderating effect of HMRP on the relationship between IA and sustainability. Keywords – Internal audit, Sustainability, Human Resources Management Practices, Armed Forces.